P199 Diabetic macular oedema (DME) and obstructive sleep apnoea (OSA)—visual improvement post CPAP therapy. Proof of principle study. (16th November 2010) - Mason, R H; Kiire, C A; Bolton, A; Smith, L; Chong, V; Stradling, J R
Abstract : Introduction and Objectives: DME is an important cause of visual loss and is more advanced in patients with coexistent OSA. 1 OSA is very common in individuals with DME (54%), compared to unselected patients with type II diabetes (23%) 2 and age matched controls (8%). 3 This study was designed to see if CPAP could improve vision in patients with DME and coexistent OSA, perhaps via a reduction in intermittent hypoxia and/or blood pressure oscillations. Methods: 35 patients with DME (identified by ocular coherence tomography, OCT) and OSA (oxygen desaturation index >10, or apnoea hypopnoea index >15) were identified. Visual acuity (VA, logMAR, similar to the Snellen chart) and OCT measurements were made twice at baseline (pre-CPAP), 3 and 6 months (post-CPAP). Results: 32 patients (17 males) participated; 4 withdrew. 28 have 3-month follow-up data and, 24 have 6-month data. Average (SD) age 66.6 years, (8.3), BMI 31.8 Kg/m 2 (6.7), HbA1c 7.5% (1.4%), ESS 7.9 (4.6), ODI 20.9 (14.8) and AHI 19.0(14.5). CPAP compliance was averaged over the 6 months and a median split into 'high' and 'low' compliers performed (> and <2.5 h/n). At 3 months VA improved significantly in both high (p=0.009) and low compliers (p=0.001). This was only sustained at 6 months in high compliers, p=0.004. (Low compliers p=0.52). There was no significant reduction in macular oedema at either 3 or n. Conclusions: This hypothesis-generating uncontrolled study indicates that continued use of CPAP in individuals with DME and OSA was associated with sustained improvement in visual acuity. This result provides justification to perform an RCT and suggests that logMAR should be the primary endpoint whereas OCT measurements appear uninformative.